ANGGARAN ANALISA PENJUALAN TERHADAP PERENCANAAN LABA PT WAHANA PERSADA KARTON PALEMBANG - Elsa Putra, Rizky; Liansyah, Irka (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study explores the strategy of sales budgeting in relation to profit planning through a combined analytical approach that includes both qualitative and quantitative methods. The author collected data through documentation, interviews, and related literature studies. The analysis results indicate that the company failed to prepare the budget effectively due to the use of a top-down (authoritarian) approach in collecting sales data from the previous year. The author suggests that the company consider using quadratic sales forecasting techniques when preparing the sales budget